Mitochondria-specific drug release and reactive oxygen species burst induced by polyprodrug nanoreactors can enhance chemotherapy - Wenjia Zhang (Nature Portfolio, 2019)
Mitochondria are a source of reactive oxygen species, which can be exploited to induce the death of cancer cells. Here, the authors use nanoparticles that release camptothecin in a reactive oxygen species dependent manner, leading to cancer cell death.